Timing of caloric intake during weight loss differentially affects striatal dopamine transporter and thalamic serotonin transporter binding. Issue 10 (5th July 2017) - Versteeg, Ruth I.; Schrantee, Anouk; Adriaanse, Sofie M.; Unmehopa, Unga A.; Booij, Jan; Reneman, Liesbeth; Fliers, Eric; la Fleur, Susanne E.; Serlie, Mireille J.
ABSTRACT: Recent studies have shown that meal timing throughout the day contributes to maintaining or regaining weight after hypocaloric diets. Although brain serotonin and dopamine are well known to be involved in regulating feeding, it is unknown whether meal timing during energy restriction affects these neurotransmitter systems. We studied the effect of a 4 wk hypocaloric diet with either 50% of daily calories consumed at breakfast (BF group) or at dinner (D group) on hypothalamic and thalamic serotonin transporter (SERT) binding and on striatal dopamine transporter (DAT) binding. The BF and D groups lost a similar amount of weight. Striatal DAT and thalamic SERT binding increased in the BF group, while decreasing in the D group after the diet (ΔDAT 0.37 ± 0.63 vs . −0.53 ± 0.77, respectively; P = 0.005; ΔSERT 0.12 ± 0.25 vs . −0.13 ± 0.26 respectively, P = 0.032). Additional voxel‐based analysis showed an increase in DAT binding in the ventral striatum in the BF group and a decrease in the dorsal striatum in the D group. During weight loss, striatal DAT and thalamic SERT binding increased weight independently when 50% of daily calories were consumed at breakfast, whereas it decreased when caloric intake was highest at dinner. These findings may contribute to the earlier reported favorable effect of meal timing on weight maintenance after hypocaloric diets.—Versteeg, R. I., Schrantee, A., Adriaanse, S. M., Unmehopa, U. A., Booij, J., Reneman, L., Fliers, E., la Fleur, S. E., Serlie, M. J. Timing of caloric intake during weight loss differentially affects striatal dopamine transporter and thalamic serotonin transporter binding. FASEB J. 31, 4545–4554 (2017). www.fasebj.org